Improvement of Human Resources of The Pamong Praja Police Unit Malaca Regency In Enforcement of Regional Regulations In Malaca Regency - Suri Leki, Michael; Djani, William; Nursalam, Nursalam (Green Publisher Indonesia, 2022)
The background of this research is how the human resources of the civil service police unit of Malacca district in enforcing regional regulations and regulations of the regional head of Malacca district, and how the level of human resources of civil service police officers can affect the enforcement of regional regulations and regional head regulations that have been determined, so that it continues to run in the corridors and discourses of peace and only have a just society, and can improve the welfare of the people in Malacca Regency. The research method used in this study uses descriptive research methods with a qualitative approach and the research techniques are observation, interviews and literature studies or literature studies with the research location at the Malacca District Civil Service Police Unit. regional head regulations that have been carried out in several sub-districts in Malacca Regency. The results of this study can be found that the resources of the Civil Service Police Unit of Malacca Regency are very necessary in implementing regional regulations and regional head regulations, so that in their implementation the apparatus in question can run in accordance with existing operational standards, so as to prevent the occurrence that may occur in the field. Therefore, every member of the civil service police unit must be given education and training as an effort to enforce existing regional regulations and regional head regulations, and in the future increase peace and can improve the people of Malacca in accordance with the ideals and expectations of the nation and society